Facilitation Of Distribution Permits, Packaging And Fresh Food Sensors Towards Improving Product Safety In Lahat Regency - Lucyana, Lucyana; Muchsiri, Mukhtarudin; Alhanannasir, Alhanannasir; Syah Putra, Nico (Biotik, 2025)
This study examines the impact of facilitation of fresh food distribution permit management including facilitation of distribution permit management procedures and packaging facilitation (type of packaging and packaging label) on improving product safety in Lahat Regency. This research method uses surveys and data analysis from fresh food producers, regulators, and consumers in Lahat Regency. Data were collected through questionnaires to understand the distribution permit process, perceptions of product safety, and the impact of the facilitation carried out. This study also uses a hedonic test to determine the quality of fresh plant-based food including assessments of color, texture, aroma and a Likert test including assessments of uniformity of size, packaging and overall appearance as well as conducting chemical contamination tests in the form of pesticide residue tests and physical contamination tests on PSAT PDUK UMKM samples for rice, coffee beans and pepper spices to determine the safety of fresh plant-based food. The results of facilitating distribution permits, packaging and fresh food sensory towards improving product safety in Lahat Regency for fresh food MSMEs have been running better than in previous years. This can be seen from the increase in the processing of PSAT-PDUK distribution permits in the period from March to July 2024 as many as 15 (fifteen) PSAT-PDUK distribution permit numbers that have been issued from 2 (two) PSAT PDUK distribution permit numbers issued by the Lahat Regency Food Security Service from 2022 to 2023, so that it can be interpreted that business actors really need special assistance from officers who understand the distribution permit processing process and an effective and efficient assistance approach model.